Peranan Psikologi Olahraga Terhadap Pencapaian Prestasi Nasional Atlet PUSLATDA Renang Indah Jawa Timur di Masa Pandemi Covid-19 - Aditria, Intan Ayu Putri; Priambodo, Anung (Universitas Singaperbangsa, 2022)
This study was aims to determine several theoretically examine the descriptive the role of sport psychology towards the national achievements of Artistic Swimming athletes of regional team in national sport week, East Java, during the covid-19 pandemic. This research uses qualitative descriptive research methods with the results of the role of sports psychology was obtained through secondary data. The data collection media used using a physical questionnaire in the form of sheets of paper that were distributed and filled to each athlete of the Artistic Swimming of regional team in national sport week, East Java, with totaling samples in this research were 6 people. This research was conducted at the Primalaras swimming pool, at Raya Darmo Harapan I street, Tanjungsari, Sukomanunggal District, Surabaya, East Java. The results of the research obtained from the research conducted there are 7 aspects that have a the role of sport psychology towards the national achievements of Artistic Swimming athletes of regional team in national sport week, East Java, during the covid-19 pandemic is motivational aspects, emotional aspects, intelligence aspects, discipline aspects, self-confidence aspects, aggressiveness aspects and self-confidence aspects.